Identifikasi Virus Penyebab Penyakit Kerdil pada Tanaman Padi di Sukamandi, Jawa Barat - Amelia Feryna Bulan Dini; I Wayan Winasa; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2015)
Viral diseases on rice is an important constraint for rice production in Indonesia. Research was conducted to determine the incidence of stunting disease in Sukamandi area at Subang regency (West Java), to identify the virus associated with the disease using RT-PCR method, and to analyze coat protein gene sequences. Field observation during growing period on November– December 2014 indicated that the incidence of stunting disease was low (0.01-10.52%). Grassy stunt and ragged stunt symptoms was observed in the fields. Spesific DNA fragments of coat protein gene of Rice ragged stunt virus (RRSV) and Rice grassy stunt virus (RGSV) was successfully amplified using specific primers. Nucleotide sequence analysis showed that RRSV and RGSV isolates from Subang has the highest homology with RRSV isolates from Vietnam, Philipines and Thailand (97.1 %) and RGSV isolate from Longan, Vietnam (95.8%), respectively.